Histopathology and Immunohistochemistry of an Atypical Case of Cutaneous Fibroma in a Crossbreed Cow - A Case Report - Siva, S,; R. Sarangabani,; Pazhanivel, N,; Ganne Venkata Sudhakar Rao, (The Indian Veterinary Journal, 2024)
Fibroma is an uncommon benign neoplasm of mesenchymal origin in animals. It arises from any site containing connective tissue including dermal and subcutaneous fibroblast. A Five year old female crossbred Jersey cow was presented to the Veterinary Dispensary. The animal had a pedunculated soft mass in its pole region. The mass was removed successfully and sent for histopathological examination in 10% neutral buffered formalin. Microscopical examination revealed a haphazard arrangement of neoplastic spindle-shaped fibrocytes, elongated to oval-shaped nuclei with indistinct eosinophilic cytoplasm, and stray mitotic figures were seen. Special staining with picrosirius red revealed positive red-coloured neoplastic fibrocytes. Immunohistochemistry examination with a vimentin marker showed a positive brown-coloured cytoplasmic reaction. Based on the gross, histopathological, special staining, and immunohistochemistry, the tumor mass was confirmed as a cutaneous fibroma.